Energy market in European Union and interests of Serbia - Rapaić Stevan (Međunarodni Problemi, 2009)
The author deals with energy market in Europe by presenting the gross consumption of energy as well as production of energy within the European Union. The need of EU for natural gas and crude oil is one of the main factors why Russia is still the key player in Europe's energy market. European Union is trying to leave Russia behind by importing crude oil and natural gas from countries like Norway, Saudi Arabia, Algeria, Libya, Nigeria, Iraq, but Europe is still highly dependent of Russian energy. Considering these facts, Serbia recognizes that its economic and political interest is to become a strategic partner with European Union as transit country for Russia's natural gas and crude oil. .